An Optimized Method to Generate Human Active Osteoclasts From Peripheral Blood Monocytes - Abdallah, Dina; Jourdain, Marie-Laure; Braux, Julien; Guillaume, Christine; Gangloff, Sophie C.; Jacquot, Jacky; Velard, Frédéric (Frontiers in Immunology, 2018)
Osteoclasts (OCs), the bone-resorbing cells, play a key role in skeletal development and adult bone remodeling. They also participate in the pathogenesis of various bone disorders. One of the major technical difficulties in the generation of OCs, when working on human material, is the ability to achieve large differentiation of mature OCs from human peripheral blood mononuclear cells (PBMCs). Access to a standardized source of active OCs is needed to better analyze the roles of human OCs. The aim of this study was to develop a procedure yielding active and mature OCs from fresh human PBMCs. We therefore examined the differentiation of PBMCs to OCs in different cell culture media, using non stripped and charcoal-stripped sera in the presence of macrophage colony-stimulating factor (M-CSF) and receptor activator of nuclear factor kappa-B ligand (RANKL). We also studied the effects of vitamin D3 in the differentiation level of PBMCs to OCs. Phalloidin-AlexaFluor®488/DAPI fluorescent stainings and dentin resorption analyses by scanning electron microscopy were used to identify the number and size of differentiated OCs, number of nuclei per cell and resorption activities of OCs for a 7-14-21-days culture period. This study reports an optimized method for an efficient production of human active OCs from a low seeding density of PBMCs, after a 14-days culture period by using a medium containing fetal bovine charcoal-stripped serum in the presence of M-CSF and RANKL, and in the absence of vitamin D3.